Social engagement after stroke – is it relevant to cognitive function? A cross-sectional analysis of UK Biobank data [version 2; peer review: 2 approved] - Carlos A. Celis-Morales; Bogna A. Drozdowska; Terence J. Quinn; Donald M. Lyall (AMRC Open Research, 2019)
Background: Findings from studies in older adult populations suggest that measures of social engagement may be associated with health outcomes, including cognitive function. Plausibly the magnitude and direction of this association may differ in stroke.  The disabling nature of stroke increases the likelihood of social isolation and stroke survivors are at high risk of cognitive decline. We assessed the association between social engagement and cognitive function in a sample of stroke survivors. Methods: We included available data from stroke survivors in the UK Biobank (N=8776; age range: 40-72; 57.4% male). In a series of regression models, we assessed cross-sectional associations between proxies of social engagement (frequency of family/friend visits, satisfaction with relationships, loneliness, opportunities to confide in someone, participation in social activities) and performance on domain specific cognitive tasks: reaction time, verbal-numerical reasoning, visual memory and prospective memory. We adjusted for demographics, health-, lifestyle-, and stroke-related factors. Accounting for multiple testing, we set our significance threshold at p<0.003. Results: After adjusting for covariates, we found independent associations between faster reaction times and monthly family visits as compared to no visit (standardised beta=-0.32, 99.7% CI: -0.61 to -0.03, N=4,930); slower reaction times and religious group participation (standardised beta=0.25, 99.7% CI 0.07 to 0.44, N=4,938); and poorer performance on both verbal-numerical reasoning and prospective memory tasks with loneliness (standardised beta=-0.19, 99.7% CI: -0.34 to -0.03, N=2,074; odds ratio=0.66, 99.7% CI: 0.46 to 0.94, N=2,188; respectively). In models where all proxies of social engagement were combined, no associations remained significant. Conclusions: We found limited task-specific associations between cognitive performance and proxies of social engagement, with only loneliness related to two tasks. Further studies are necessary to confirm and improve our understanding of these relationships and investigate the potential to target psychosocial factors to support cognitive function in stroke survivors.